Supply side evidence of Myanmar’s growing agricultural mechanization market - Win, Myat Thida; Thinzar, Aye Mya; Zu, A Myint (Michigan State University, 2018)
Recent evidence suggests that the mechanization of agriculture is proceeding rapidly in areas of Myanmar close to the country’s major city, Yangon, as farmers - driven by the need to remain profitable in the face of labor shortages and rising wage rates - adopt a variety of labor saving technologies (Win and Thinzar 2016). In this brief, we present findings from the first survey in Myanmar to analyze the supply side of agricultural mechanization. We find evidence of rapid growth in the number, geographical distribution, and sales of agricultural machinery supply businesses. The range and value of machinery sold accelerated rapidly, especially post-2011 as the country opened economically. New hire-purchase financing arrangements for machinery played a key role in facilitating this growth.